Smartchain: a blockchain-based user authentication system for smart homes - Islam, Mushaidul; Hossain, Mohammed Sayeem Sadat; Das, Shijon (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.